ASSESSMENT TOOLS IN THE ENGLISH CLASSROOM: EVALUATING THEIR EFFECTIVENESS - Tatyana Trigulova; Madinabonu Fayzullayeva (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: Effective assessment is a crucial component of English language instruction, as it allows educators to gauge student progress, identify areas for improvement, and tailor their teaching strategies accordingly. This article explores the diverse range of assessment tools utilized in the English classroom and examines their respective strengths and limitations. Through a review of empirical research and case studies, the article presents a comprehensive analysis of the effectiveness of formative, summative, and alternative assessment methods, including standardized tests, performance-based assessments, and portfolio-based evaluations. The findings of this study offer valuable insights for English language teachers, curriculum designers, and educational policymakers, highlighting the importance of adopting a balanced and holistic approach to student assessment.